The rights of slaves in the Crimean Khanate and the conditions for their emancipation - Rustemov O.D. (Золотоордынское обозрение)
Research objectives: The aim of this research is to study issues related to the legal status of slaves, as well as the terms and conditions of their release in the Crimean Khanate. Research materials: Individual research works on the topic of slavery in Ottoman Turkey and the texts of the Crimean Kadiasker books (sijils) in which slaves appear in connection with various legal proceedings related to them. Results and novelty of the research: Novelty lies in the fact that certain terms from the history of slavery in the Turkic Muslim states have been introduced into scientific circulation. For the first time in Russian historiography, the so-called guarantees (tedbir) of the liberation of slaves in the Crimean Khanate are described. The practice of announcing such “guarantees” to slaves finds its confirmation in court documents of the 17th century. The question of the existence of a limiting service life of slaves in the Crimean Khanate is considered. Also, for the first time, using historical evidence, the legal status of slaves has been studied, the relationship between slaves and masters has been examined, and other reasons for the release of slaves, not related to the end of their service, have been identified. As a result of this study, it is established that in the Crimea of the 16th-18th centuries, according to Muslim law, only prisoners of war captured in a war or on a campaign could become slaves. According to Sharia, Muslims could not be enslaved. This rule was strictly adhered to in the Crimea. We find confirmation of this fact in individual Crimean sijils where the fate of the Lipka Tatars who, being Muslims, were captured, brought to Crimea, and subsequently released. Such documents are examined here. The study has found that slaves were deprived of legal rights and had the status of mütekavvım mal – property permitted for use. They were part of the common property that could be sold, exchanged, donated, or used at the discretion of the owner. In yafts or lists of inherited property, slaves were listed, as a rule, among animals or other things. Sometimes slaves, at the request of their masters, received additional powers and became semi-free traders. A special category of slaves that stood out among others should be noted among the soldiers of the khan’s guard – kapy-kulu (literally – slave of the door/slave at the gate). This article determines that the normal life of a slave corresponded to a full six years. In addition to release on the grounds of seniority, other conditions for the release of a slave were also possible. Four types of tedbir and the conditions of kitabet, or an agreement on the independent redemption of oneself by a slave, are considered. Cases of the release of slaves on religious grounds are described, and the possibilities for them to go to court for legal assistance are described. All the facts of legal precedents given in the article are supported by information from the Crimean Cadi sijils. In conclusion, concepts are given regarding the system of slavery adopted in the khanate.